Current Management of Obstetric Fistula: Implication for the Low Resource Areas - Jackson Umoiyoho, Aniefiok; Emurobohwo Ugege, Wilson (Current Women's Health Reviews, 2013)
Obstetric fistula is a form of maternal morbidity which may occur in any woman of reproductive age who suffers from prolonged obstructed labor or traumatic attempt at vaginal delivery. The medical and social consequences of obstetric fistula can be life-shattering for women, their children and families. The principles of obstetric fistula repair have changed very little over the years, though a number of them are often modified by the cost, efficacy of treatment modality, and skill of the surgeon. Advances in other areas of surgery such as laparoscopic surgery have led to more precise identification of fistulous urogenital tracts and improved precision of tissue plane dissection and repair. Robotic surgery was a significant improvement in laparoscopy. It reduces operating fatigue and eliminates unpredictable movements and tremors common with human hands during laparoscopy. The introduction and wide spread use of surgical glue will ultimately reduce the need for interpositional tissue flaps. However, unavailability of resources to deploy these current trends in the management of obstetric fistula in resource poor setting may limit the use of these modalities in such areas where most of the cases occur.
Keywords: maternal morbidity